Mycobiome in the Lower Respiratory Tract – A Clinical Perspective - Krause, Robert; Moissl-Eichinger, Christine; Halwachs, Bettina; Gorkiewicz, Gregor; Berg, Gabriele; Valentin, Thomas; Prattes, Jürgen; Högenauer, Christoph; Zollner-Schwetz, Ines (Frontiers in Microbiology, 2017)
Recently the paradigm that the healthy lung is sterile was challenged and it is now believed that the lungs harbor a diverse microbiota also contributing to the pathogenesis of various diseases. Most of the research studies targeting the respiratory microbiome have focused on bacteria and their impact on lung health and lung diseases. Recently, also the mycobiome has gained attention. Lower respiratory tract (LRT) diseases (e.g cystic fibrosis) and other diseases or conditions (e.g. HIV infection, lung transplantation, treatment at intensive care units) have been investigated with regard to possible involvement of mycobiome in development or progression of diseases. It has been shown that diversities of mycobiome in the LRT vary in different populations and conditions. It has been proposed that the mycobiome diversity associated with LRT can vary with different stages of diseases. Overall, Candida was the dominant fungal genus in LRT samples. In this review, we summarize the recent findings regarding the human LRT mycobiome from a clinical perspective focussing on characterization of investigated patient groups and healthy controls as well as sampling techniques. From these data, clinical implications for further studies or routine practice are drawn. To obtain clinically relevant answers efforts should be enhanced to collect well characterized and described patient groups as well as healthy individuals for comparative data analysis and to apply thorough sampling techniques. We need to proceed with elucidation of the role of mycobiota in healthy LRT and LRT diseases to hopefully improve patient care.